The role of new media tools in supporting health awareness for the protection of the Covaid 19 virus - Adnan Burhan Qadir; Sabah Ahmad Najar (Zanco Journal of Humanity Sciences)
The world has made big changes in the 21st century, and the main reason for this change is the advancement of technology, which is a skilled home and events are being moved very quickly, and so on. he has expanded his understanding and family and electronic relationships, and has accelerated his slow work in the area from moving them into homes and the only chickens in the coma The lga, therefore, has crossed the political and geographical boundaries of human activities, organisations and countries, and has delivered all kinds of services to humanbeings in all its forms, reconstructing the lives of individuals in a new way.